Penanaman Apotik Hidup Dan Kebersihan Lingkungan - Utama, Agustian; Susanti, Apriani; Pasaribu, Ayu Maya Sari; Zahran, Muhammad; Saputra, Alwi; Akbar, Anjas Siratul; Moulina, Methatias Ayu; Nuraini, Hesti; Fariadi, Herri (Universitas Dehasen Bengkulu, 2025)
To improve environmental quality, environmental knowledge has an important role in preserving the environment, because through knowledge humans increasingly understand and are aware of the dangers of household waste to the environment, especially the dangers of pollution to human health. Family income is any form of remuneration obtained as reward or remuneration for someone's contribution to the production process. Family income can come from one's own business (self-employment), work for other people, and income from property (assets). It is not that housewives, farmers and traders do not want to make goods from recycled plastic waste in their efforts to make them into new goods that are useful and have added economic value, but because they do not know what economic added value is and the processing of plastic waste and what the benefits are for increasing The income they get from their families can be seen from their enthusiasm during community service activities, even at the end of the activity, all participants expressed their gratitude for having been taught about processing plastic waste into new items that are useful and of high economic value and hope that they will continue to be accompanied and continue to hold activities like this.